2002
DOI: 10.1097/00130404-200201000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Dose/Volume Relationship of Late Rectal Bleeding After External Beam Radiotherapy for Localized Prostate Cancer

Abstract: To date, five patients have had grade 1 late rectal toxicity (one CRT case and four SCIM-RT cases), one patient had grade 2 late rectal toxicity (CRT), and three patients had grade 3 late rectal toxicity (all CRT cases). Because of the low number of events, the analysis was performed with all patients experiencing rectal bleeding grouped together. The actuarial rectal bleeding rates at 18 and 24 months were 6% and 8%, respectively. The actuarial rectal bleeding rates at 24 months were identical (8%) for both S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…This interpretation was based on the planning data and the recommendation that not more than 15 cc of the planned rectal volume should receive the prescribed dose. [17] In our study, the above planning constraint was met in all the patients and only six of the 187 (3.2%) treatment fractions analysed had a rectal volume of >15cc (and all less than 17cc) receiving the prescribed dose. This is an encouraging finding and may be attributed to the daily soft tissue image guidance used.…”
Section: Discussionmentioning
confidence: 70%
“…This interpretation was based on the planning data and the recommendation that not more than 15 cc of the planned rectal volume should receive the prescribed dose. [17] In our study, the above planning constraint was met in all the patients and only six of the 187 (3.2%) treatment fractions analysed had a rectal volume of >15cc (and all less than 17cc) receiving the prescribed dose. This is an encouraging finding and may be attributed to the daily soft tissue image guidance used.…”
Section: Discussionmentioning
confidence: 70%
“…28,29 However, as shown by Kupelian et al, rising PSA after curatively intended local treatment in general predicts the development of clinical progression, often after long intervals. 30 Pound et al reported that PSA progression preceded the diagnosis of distant metastases by a median time of 8 years after radical prostatectomy. 31 ASTRO has published guidelines for identification of patients with biochemical failure after definitive radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Preferably, data used for NTCP analyses should include the full organ volume (see reference (19): page 107, paragraph 2). When this is not possible, either a standard method of normalization, or absolute volumes should be used (see reference (21): page 63 Methods and Materials paragraph 2, and table 1). A clear statement of the definition of the organ volume should be given, paying close attention to such issues as length of linear structures included (e.g.…”
Section: Requirements For Future Quantec Effortsmentioning
confidence: 99%